Effect of sacubitril/valsartan on cognitive function in patients with HFpEF: a prespecified analysis of PARAGON-HF. (25th November 2020) - Dewan, P; Jhund, P.S; Anand, I.S; Desai, A.S; Gong, J; Lefkowitz, M.P; Pieske, B; Rizkala, A.R; Shah, S.J; Van Veldhuisen, D.J; Zannad, F; Zile, M.R; et al.
Abstract: Background: A theoretical concern has been raised about detrimental effects of sacubitril/valsartan (sac/val) on cognitive function as neprilysin is one of many pathways involved in clearance of amyloid beta peptides from brain tissue. Purpose: To examine effect of sac/val, compared with valsartan, on cognitive function in patients with heart failure (HF) and preserved ejection fraction (HFpEF). Methods: In the PARAGON-HF trial, cognitive function was tested in a subgroup of patients at baseline and follow-up, using Mini-Mental State Examination [MMSE] having a maximum score of 30 (higher scores reflect better cognitive function). Change in MMSE score from baseline to 96 wks was a prespecified exploratory endpoint. Other post hoc analyses included "cognitive decline" (fall in MMSE ≥3 pts) and assessment of cognition-related adverse events (AEs). Results: Among 2895 patients (60% of total) in PARAGON-HF with baseline MMSE measurement, mean (SD) score was 27.4 (3.0) in patients receiving sac/val (1453) and 27.4 (2.9) in patients receiving valsartan (1442). There was no difference between sac/val and valsartan in MMSE score change from baseline to wk 96: sac/val −0.02 (SE 0.07) and valsartan 0.00 (0.07); between-treatment difference −0.02 (95% CI: −0.22 to 0.18); p-value = 0.83. Cognitive decline at 96 weeks occurred in 115 of 1071 evaluable patients (10.7%) in sac/val group and 121 of 1053 patients (11.5%) in valsartan group; risk ratio 0.97 (0.75–1.26), p-value = 0.82. Cognition-related AEs were more frequent, than in PARADIGM-HF (likely as patients in PARAGON-HF were older) but, as in PARADIGM-HF, did not differ between sac/val and comparator treatment (Table). Conclusions: Cognitive change, measured by MMSE, did not differ between treatment with sac/val & valsartan in patients with HFpEF. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): PARAGON-HF study was funded by Novartis Pharma.